2007
DOI: 10.1161/circulationaha.106.675934
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stent and Coronary Thrombosis

Abstract: Abstract-Although rare, stent thrombosis remains a severe complication after stent implantation owing to its high morbidity and mortality. Since the introduction of drug-eluting stents (DES), most interventional centers have noted stent thrombosis up to 3 years after implantation, a complication rarely seen with bare-metal stents. Some data from large registries and meta-analyses of randomized trials indicate a higher risk for DES thrombosis, whereas others suggest an absence of such a risk. Several factors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
233
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 824 publications
(248 citation statements)
references
References 67 publications
5
233
1
9
Order By: Relevance
“…Findings from the present study reinforce the concept that DMSO is an interesting alternative for the coating of DES where currently employed drugs do not completely address the risks of stent thrombosis [4,5,14,15,17,20,31,34] and, in addition, were shown to induce the expression of TF [29,32,38].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Findings from the present study reinforce the concept that DMSO is an interesting alternative for the coating of DES where currently employed drugs do not completely address the risks of stent thrombosis [4,5,14,15,17,20,31,34] and, in addition, were shown to induce the expression of TF [29,32,38].…”
Section: Discussionsupporting
confidence: 71%
“…Even though coronary bare metal stents (BMS) and drug-eluting stent (DES) implantation greatly improved prognosis of ACS patients, acute and sub-acute stent thrombosis still remain a serious concern [4,5,14,15,17,20,31,34]. In line with this, we recently showed that drugs released from DES enhance tissue factor (TF), a key trigger for thrombosis and thus could play a paradoxical role in eliciting stent thrombosis [29,32].…”
Section: Introductionmentioning
confidence: 96%
“…14 The incidence of stent thrombosis in the modern era of stent deployment varies from a low of 0.5% to 1.9% with BMS implantation, the same as with DES implantation. [15][16][17] To prevent stent thrombosis, clopidogrel 75 mg/day should be given for at least 6 months after DES implantation and, ideally, up to 12 months in patients who are not at high risk of bleeding, but there has been debate regarding how long such therapy should continue.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first 30 days, the frequency of stent thrombosis is similar after either bare metal stent or drug-eluting stent (DES) implantation, when dual antiplatelet therapy is maintained (1). Recently, concerns have emerged about the high risk of late stent thrombosis (more than 30 days) after DES implantation due to delayed coronary endothelization, late stent malapposition or aneurysm formation (2). Based on a meta-analysis of multicentre, randomized studies, the predicting factors of late stent thrombosis include stent length and the discontinuation or ineffectiveness of thienopyridine-based antiplatelet therapy (1).…”
mentioning
confidence: 99%